2012
DOI: 10.1002/ebch.1819
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane Review: Nonsteroidal anti‐inflammatory drugs and perioperative bleeding in paediatric tonsillectomy

Abstract: BackgroundNonsteroidal anti‐inflammatory drugs (NSAIDs) are used for pain relief following tonsillectomy in children. However, as they inhibit platelet aggregation and prolong bleeding time, they could cause increased perioperative bleeding. The overall risk remains unclear. This review was originally published in 2004 and was updated in 2010.ObjectivesThe primary objective of this review was to assess the effects of NSAIDs on bleeding with paediatric tonsillectomy. Our secondary outcome was to establish wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…A large randomized controlled trial was unable to exclude an increased risk of severe bleeding with ibuprofen compared with acetaminophen after tonsillectomy, 27 and recently a prospective study demonstrated a reduction in post-tonsillectomy hemorrhage rates from 5% to less than 1% by increasing the dosing interval of oral ibuprofen (10 mg/kg) from 6 to 8 h. 45 Systematic reviews are equivocal regarding NSAIDs after tonsillectomy and are limited by a number of factors including: insufficient pediatric subjects, heterogeneity in diagnostic indication for adenotonsillectomy, surgical approach and technique, and variable NSAID type, dose, and perioperative timing studied, among others. 16,18,46–48 Finally, a recent meta-analysis of ibuprofen concluded an increased post-tonsillectomy hemorrhage odds ratio of 1.38 (95% CI, 1.11 to 1.72). 49 Given the uncertain risk of bleeding with nonselective NSAIDs, the benefits of COX-2–specific inhibitors in terms of analgesic efficacy and platelet sparing effects, even at supra-therapeutic plasma levels, 19 are noteworthy and have been the focus of a recent meta-analysis 21 and demonstrated in five randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large randomized controlled trial was unable to exclude an increased risk of severe bleeding with ibuprofen compared with acetaminophen after tonsillectomy, 27 and recently a prospective study demonstrated a reduction in post-tonsillectomy hemorrhage rates from 5% to less than 1% by increasing the dosing interval of oral ibuprofen (10 mg/kg) from 6 to 8 h. 45 Systematic reviews are equivocal regarding NSAIDs after tonsillectomy and are limited by a number of factors including: insufficient pediatric subjects, heterogeneity in diagnostic indication for adenotonsillectomy, surgical approach and technique, and variable NSAID type, dose, and perioperative timing studied, among others. 16,18,46–48 Finally, a recent meta-analysis of ibuprofen concluded an increased post-tonsillectomy hemorrhage odds ratio of 1.38 (95% CI, 1.11 to 1.72). 49 Given the uncertain risk of bleeding with nonselective NSAIDs, the benefits of COX-2–specific inhibitors in terms of analgesic efficacy and platelet sparing effects, even at supra-therapeutic plasma levels, 19 are noteworthy and have been the focus of a recent meta-analysis 21 and demonstrated in five randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Although small cohort studies support the use of nonselective NSAIDs, reporting no changes in frequency of bleeding, 13 evidence suggests they may increase post-tonsillectomy hemorrhage severity. 14 Additionally, systematic reviews cite insufficient evidence to discount bleeding risks in children 15,16 due to inadequate sample sizes to assess rare (less than 5%) bleeding events 15–17 or inclusion of both children and adults in larger cohort studies. 18 Given that nonselective NSAID safety is unclear, there is interest in studying other agents, including COX-2 selective inhibitors ( e.g.…”
mentioning
confidence: 99%
“…This may lead to high heterogeneity and ultimately affect the results. (9) The primary endpoints were analyzed at 24, 48, and 72 h after operation. However, given that the included studies did not mention the time point at which adverse reactions were recorded, subgroup analysis of secondary endpoints was not conducted according to time (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the key enzymes that initiate inflammatory reactions and promote inflammatory response leading to tissue injury [8]. NSAIDs, therefore, simultaneously exert anti-inflammation and analgesic effects which also increases the risk of perioperative bleeding and digestive tract symptoms [9]. Selective COX-2 inhibitors not only prevent inflammation and exert analgesic and antipyretic effects, but also protect the gastrointestinal mucosa and are widely used in orthopedic postoperative analgesia [10].…”
Section: Introductionmentioning
confidence: 99%